Two essays on economic growth and the relative price of capital - Silva, Dejanir Henrique (2012)
This dissertation consists in an analysis about the interconnection between the relative price of capital and economic growth. The work is divided in two essays. In the first one, an analysis of the dynamic impact of trade restrictions is performed in order to understand the impact over economic growth and relative price of capital. This analysis is particularly relevant to understand the Brazilian case, which presented a strong rise in the relative price of capital, exactly at the time the country was adopting import substitution policies and restrictions to the trade of capital goods. The second essay emphasizes differences between countries of income per capita and relative price of capital. Consistent with recent empirical work, this analysis emphasizes how differences in productivity could be generated and how this could impact the dispersion of income per capita and the relative price of capital.